Personal and Social Factors of Motivation Across the Performance of Women Entrepreneurs in Israel - Farraj, Hedal (Digital Repository of Theses - SSBM Geneva, 2025)
Despite the growing startup scene in Israel, women still face substantial obstacles when it comes to entrepreneurship. Even if Israel's rate of female entrepreneurship is higher than that of other nations, there is still a significant gap in terms of funding, connections, and government assistance initiatives targeted at small and medium-sized female businesses. A specific problem with female entrepreneurs in Israel concerns the lack of personal and social motivation factors that influence their business performance, as well as the lack of documented linkages between personal, social, and economic expansion. The purpose of this qualitative study was to achieve a deeper understanding of how motivation factors contribute to business performance; in the context of small-sized enterprises owned by women entrepreneurs, and how women entrepreneurs in Israel operate their enterprises while balancing responsibilities and commitments. The study used a qualitative methodology to assess the complex factors influencing the entrepreneurial journey of 20 female entrepreneurs, based on the semi-structured interviews. The study findings clearly indicated that entrepreneurial high performance is deeply tied to factors such as strong relationships and support systems, empowerment through autonomy, personal growth, the desire for financial security, and gender identity. These findings revealed the importance of holistic strategies for work-life harmony, including effective time management, adopting digital tools, and fostering professional networks. Flexible scheduling and family support emerged as pivotal in enabling these women to sustain their entrepreneurial endeavors while meeting personal obligations. This study contributed to the theoretical understanding of women’s entrepreneurship by offering an integrated perspective on personal and social motivation factors. The findings were compared with secondary data and offered practical implications for policymakers, corporate leaders, and educators, to design programs and initiatives that empower female entrepreneurs. Future research can validate the findings of this study using larger sample sizes and may examine deeply the moderating effect of a social mission on the relationships identified in this study. Keywords: motivational factors, female entrepreneurs, business performance, Israel